Automation, digitalization and decarbonization in the European automotive industry: A roadmap towards a just transition - Armanda Cetrulo; Giovanni Dosi; Angelo Moro; Linnea Nelli; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This position paper outlines the characteristics of the trends at stake in affecting the twin transition in the European automotive industry, and the political economy of the actors behind such transition. We first describe the automation and digitalization processes in the automotive sector and their effects on employment. Possible scenarios are analysed, illustrating actual cases of electrification conversion of some European plants of the key OEMs companies as practical examples to understand the employment effects. We then consider the role of the regulatory push in fostering the transition of the automotive sector towards electrification, highlighting the non-neutrality of the process and the risk of a quite limited space for decarbonization. Finally, we discuss the space and capacity of trade unions' actions to orient the twin transition toward social and climate justice.
Keywords: J5; L6; O2; O3; 330; Social dialogue; trade unions; employment; political economy